Vectorcardiographic features of ventricular extrasystoles correlated with conventional scalar electrocardiographic interpretation. Issue 8 (August 1978) - Talbot, S; Kilpatrick, D; Weeks, B
Abstract : Horizontal and frontal plane QRS loops of patients in sinus rhythm with uniform ventricular extrasystoles were constructed from digitised Frank orthogonal electrocardiograms. In 4 patients ventricular extrasystoles were indistinguishable from right bundle-branch complexes, and in another they were indistinguishable from left bundle-branch complexes. In 25 patients ventricular extrasystoles showed an initial delay (greater than or equal to 20 ms) of the QRS, followed by an R loop, which in 13 patients resembled left bundle-branch block complexes, and in 12 patients resembled right bundle-branch block complexes, with an anterior clockwise loop in the horizontal plane. However, the frontal plane loop often did not resemble that of either right or left bundle-branch block. In 51 patients ventricular extrasystoles had an initial delay which was prolonged into the efferent limb of the QRS loop with acceleration of the afferent limb, and/or the QRS loop was directed anteriorly, inferiorly, and to the left. Conventional recordings of these extrasystoles usually showed an initial slow upstroke (or downstroke) of the QRS resembling a delta wave. Apparently uniform ventricular extrasystoles on scalar recordings were shown to be multiform vectorcardiographically though in all such cases the direction of the initial 40 ms forces was constant. It is suggested that the slow initial inscription of ventricular extrasystoles is the result of excitation of ventricular muscle directly and not through specialised His-Purkinje fibres, and that the direction of such initial forces may indicate the ventricular origin of ventricular extrasystoles.